Composite Material Innovation in Automotive Structure Applications - Faizal herum ibrahim; Agus priyanto; Sigit saifudin; Andi eko saputro; Ikhwanul Qiram (Fakultas Teknik Universitas PGRI Banyuwangi, 2025)
The use of composite materials in the automotive industry has become a critical topic over the past decade, driven by increasing demands for lightweight, fuel-efficient, and environmentally friendly vehicles. This review examines the development and application of composite materials—particularly Carbon Fiber Reinforced Polymer (CFRP) and Glass Fiber Reinforced Polymer (GFRP)—in automotive structural components. The study employs a systematic literature review of 15 scholarly sources from databases such as Scopus, Google Scholar, and ScienceDirect, with inclusion criteria focusing on peer-reviewed publications (2014–2024) relevant to mechanical engineering and automotive applications. The findings indicate that CFRP and GFRP can reduce vehicle weight by 30–40%, significantly improving fuel efficiency and reducing carbon emissions. However, challenges such as high production costs, complex manufacturing processes, and recycling limitations hinder widespread adoption. Recent trends highlight growing interest in bio-based and hybrid composites, alongside advancements in manufacturing technologies like resin transfer molding (RTM) and automated fiber placement (AFP) as potential solutions. In conclusion, composite materials hold immense potential for automotive innovation, but further research is needed to integrate material science, manufacturing scalability, cost-effectiveness, and environmental sustainability to ensure long-term viability